Which csr activities are preferred by local community residents? Conjoint and cluster analyses - Siraprapa Panthong (2022)
Industrial estates (IEs) are important for economic growth, but they also negatively impact the living environment of local communities. To foster community acceptance, IEs and companies often implement corporate social responsibility (CSR) programs. However, very few studies have explored the preferences of local communities. Therefore, the first objective of this research was to identify the CSR dimensions and activities preferred by local communities surrounding Amata City Industrial Estate in Chonburi, Thailand, while the second objective was to categorize residents based on their CSR preferences using K‐means clustering. Data were collected from 309 residents and assessed using a choice‐based conjoint analysis, with the two most preferred CSR dimensions identified as economy and environment. The results confirmed heterogeneity within a community. Seven segments were identified as wellness enthusiasts, sustainable developers, knowledge sup-porters, balanced conservators, nature lovers, utilitarian developers and economic persons. The findings should be beneficial for IE management in Thailand and could be used by companies and local governments to initiate citizen‐centric CSR activities.